Semi-interpenetrating network cellulose-based hydrocolloid material for spinning as well as preparation method and application of semi-interpenetrating network cellulose-based hydrocolloid material

By using a pure water system to prepare semi-interpenetrating network cellulose-based aqueous colloids in the industrial production of cellulose fibers, the problems of solvent pollution and process complexity are solved, and the green processing of cellulose fibers and high-performance spinning are achieved.

CN119161594AActive Publication Date: 2024-12-20SICHUAN UNIV

Patent Information

Application Number
CN202411409793.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2024-12-20
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

The industrial production of existing cellulose fibers has problems such as serious solvent pollution, complex process and high cost, making it difficult to achieve green processing.

Method used

A pure water system is used to prepare semi-interpenetrating network cellulose-based aqueous colloidal material, and a homogeneous cellulose aqueous colloid dispersion is obtained through mechanical shearing and chemical crosslinking, and cellulose aqueous colloid is used as the first component, an aqueous polymer As the second component, a semi-interpenetrating network is formed to realize cellulose spinning.

Benefits of technology

The green processing of cellulose fibers has been achieved, pollution and process complexity have been reduced, the spinning and mechanical properties of cellulose fibers have the potential for industrial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161594A_ABST
    Figure CN119161594A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of cellulose spinning, and discloses a semi-interpenetrating network cellulose-based hydrocolloid material for spinning and a preparation method and application thereof.The method comprises the steps that cellulose pulp is subjected to homogenization treatment in water after being mechanically sheared, and fibrillated cellulose dispersion liquid is obtained; adding a cross-linking agent to form a cellulose aqueous colloidal solution; the preparation method comprises the following steps: adding a water-based polymer into a cellulose water-based colloidal solution, stirring and dissolving, and adding an initiator and a cross-linking agent to prepare the semi-interpenetrating network cellulose-based water-based colloid with spinnability. The preparation method is different from a cellulose solvent system, a pure water system instead of an organic solvent system is adopted, and the problems of complex process, high energy consumption, pollutant discharge and the like in the cellulose dissolving process are solved. The invention of the technology is expected to realize the green processing and manufacturing of the cellulose-based fiber in a real sense, and provides a new technical direction for the green processing and manufacturing and deep development of the cellulose fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cellulose spinning, and in particular to a semi-interpenetrating network cellulose-based aqueous colloid material for spinning, and a preparation method and application thereof. Background Art

[0002] In recent years, with the purpose of reducing and replacing petrochemical resources, the research on fiber resource pathways of cellulose-based biomass has received more attention from academia and industry, especially the processing and manufacturing of regenerated cellulose fibers. However, the current commercial regenerated cellulose fibers are limited by the complex and expensive production process and serious pollution of the solvent system, making it difficult to achieve the real green processing and development of cellulose fibers. This is mainly attributed to the fact that the crystalline structure of cellulose limits the movement and arrangement of molecular chains, making it difficult to process. At present, the industrial production of cellulose fibers is mainly based on solvent systems, but there are many problems of its own. For example, the viscose process has a lengthy processing process and the generation of pollutants CS2, the lyocell process raw material NMMO is difficult to synthesize, is mainly imported at a high price, is easy to decompose at high temperature, and has important quality problems such as easy fibrillation of wet fibers; and the relatively green low-temperature alkaline urea system and ionic liquid system still face many challenges in industrialization due to their own defects (such as solvent recovery costs and process equipment). Therefore, the preparation of high-quality cellulose spinning solution based on green processing is particularly important for the green and environmentally friendly industrial production and development of cellulose fibers.

[0003] In the prior art disclosed about cellulose colloid solution, Chinese Patent No. CN116396405A discloses a method for preparing microcrystalline cellulose colloid based on straw pith, wherein the pretreated straw pith raw material is added to alkali solution and soaked for a certain period of time, and then the alkali solution is filtered out, crushed, sheared, dispersed, filtered and washed to obtain stably dispersed microcrystalline cellulose colloid; Chinese Patent No. CN103304824A discloses a method for preparing high-concentration nano-microcrystalline cellulose colloid, wherein a low-concentration nano-microcrystalline cellulose dispersion is prepared by sulfuric acid hydrolysis, and then water is removed by rotary evaporation to obtain a 35-85 mass fraction nano-microcrystalline cellulose dispersion. wt% nanocrystalline cellulose colloid; Chinese patent number CN104072787B also discloses a method for preparing a high-concentration nanocellulose colloid, the invention prepares nanocellulose by mechanical method, chemical method, biological method or mechanochemical method, the obtained nanocellulose is separated by centrifugation or microporous filter cloth filtration to obtain nanocellulose colloid, then the nanocellulose colloid is frozen at low temperature to form aggregation and entanglement between the nanocellulose, and then the frozen nanocellulose colloid is placed at 0 oC or above, and finally the precipitate is dispersed in a solvent by filtering, filtering, washing and mechanical shearing to obtain a high-concentration nanocellulose colloid; Chinese patent numbers CN107090607B and CN113150314B both disclose inventive technologies for preparing composite fibers or gel materials by mixing cellulose dissolving liquid with polyvinyl alcohol components based on a cellulose solvent system. There is no relevant report on this green processing technology for preparing cellulose-based aqueous colloids with good spinnability in the above-mentioned public inventions. Summary of the invention

[0004] The existing production processes of regenerated cellulose fibers are limited by the cellulose dissolution process-solvent system, such as serious pollution emissions, expensive solvents, complex dissolution processes and equipment, and difficulty in solvent recovery, making it difficult to truly achieve green production and processing of cellulose fibers. The present invention aims to solve the above technical problems existing in existing production, and provides a semi-interpenetrating network cellulose-based aqueous colloid material for cellulose spinning based on a pure water system, and its preparation method and application.

[0005] To achieve the above object, on the one hand, the present invention provides a method for preparing a semi-interpenetrating network cellulose-based aqueous colloid material for spinning, which comprises the following steps:

[0006] S1. Using cellulose pulp as raw material, obtaining micro / nano-fibrillated cellulose of uniform fineness by mechanical shearing, then preparing an aqueous suspension of fibrillated cellulose with water as solvent, and then obtaining a non-derivatized fibrillated cellulose dispersion with a solid content of 2-20 wt% by homogenization;

[0007] S2, adding a crosslinking agent to the fibrillated cellulose dispersion obtained in step S1, and stirring the mixture at a constant temperature to obtain a uniform cellulose aqueous colloidal solution having a solid content of 2.1-24 wt%, wherein the cellulose aqueous colloidal solution is a network crosslinked solution based on covalent bonds or hydrogen bonds between cellulose and the crosslinking agent, wherein the mass ratio of cellulose to the crosslinking agent is 1:0.05-1:0.2, and the crosslinking agent is at least one of epichlorohydrin, glutaraldehyde, tannic acid, citric acid, sodium alginate, calcium chloride, and ferrous chloride;

[0008] S3, using the cellulose aqueous colloid solution obtained in step S2 as the first component - cellulose aqueous solution, adding monomers or prepolymers of aqueous polymers into the first component - cellulose aqueous solution, stirring and dissolving, and adding initiators and cross-linking agents, so that the monomers or prepolymers of aqueous polymers are in situ polymerized and cross-linked in the first component - cellulose aqueous solution under the action of the initiators and cross-linking agents to form a second component - polymer network, and finally obtaining a semi-interpenetrating network cellulose-based aqueous colloid with certain spinnability, wherein the mass ratio of cellulose to aqueous polymer is 1:0.1-1:1, and the solid content of the obtained semi-interpenetrating network cellulose-based aqueous colloid is 2.3-46 wt%.

[0009] As a further preferred technical solution of the present invention, the cellulose pulp in step S1 is any one of wood pulp, cotton pulp, bamboo pulp, hemp pulp and straw pulp, or bacterial cellulose.

[0010] As a further preferred technical solution of the present invention, the mechanical shearing treatment method in step S1 is one or more of high-pressure homogenization, disc milling, ball milling, pulverizer crushing, steam explosion, twin-screw kneading, and mechanical stirring crushing.

[0011] As a further preferred technical solution of the present invention, in step S2, the temperature of sufficient stirring is 20-90 o C, time is 4-24 h.

[0012] As a further preferred technical solution of the present invention, in step S3, the aqueous polymer is any one of polyacrylamide, polyvinyl pyrrolidone, polyethylene oxide, polyethylene glycol, sodium polyacrylate, and polyvinyl alcohol.

[0013] As a further preferred technical solution of the present invention, in step S3, the mass ratio of the aqueous polymer monomer to the initiator is 1:0.005-1:0.015, and the mass ratio of the aqueous polymer to the crosslinking agent is 1:0.01-1:0.2.

[0014] As a further preferred technical solution of the present invention, in step S3, the initiator is at least one of potassium persulfate, sodium persulfate, azobisisobutyronitrile, and methylmagnesium bromide, and the crosslinking agent is at least one of N,N'-methylenebisacrylamide and glutaraldehyde.

[0015] According to another aspect of the present invention, the present invention also provides a semi-interpenetrating network cellulose-based aqueous colloid material, which is prepared by the above method.

[0016] According to another aspect of the present invention, the present invention also provides an application of a semi-interpenetrating network cellulose-based aqueous colloid material in spinning, and wet spinning can be used to produce fibers.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The invention uses natural cellulose pulp as raw material and water as solvent, obtains homogeneous cellulose aqueous colloid dispersion by mechanical shearing and chemical cross-linking, then uses cellulose aqueous colloid as the first component and aqueous polymer as the second component to interpenetrate with the first component to form a semi-interpenetrating network, and the obtained semi-interpenetrating network cellulose-based aqueous colloid has certain spinnability.

[0019] The semi-interpenetrating network cellulose-based aqueous colloidal spinning solution prepared by the present invention is based on green processing in a water system, which is different from the dissolution processing technology of a solvent system, that is, the preparation process is pollution-free and the process is green and environmentally friendly, realizing the green processing and manufacturing of cellulose-based fibers in a water system in a true sense. This technology has great reference significance for the green processing and in-depth development of cellulose fibers. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0021] Figure 1 The figures are the physical pictures of the semi-interpenetrating network cellulose-based aqueous colloids with different cellulose contents in Examples 1-3, wherein a, b and c are the semi-interpenetrating network cellulose-based aqueous colloids with spinnability and cellulose contents of 6 wt%, 10 wt% and 14 wt%, respectively, and the corresponding solid contents are 10 wt%, 16.6 wt% and 22.3 wt%, respectively;

[0022] Figure 2 The figures are as follows: cellulose-based fibers obtained by wet spinning a semi-interpenetrating network cellulose-based aqueous colloid (solid content 10 wt%) with a cellulose content of 6 wt% in Example 2, and the single fiber strength-elongation relationship curve and the fiber surface and cross-sectional morphology measured by optical microscopy, wherein a is the cellulose-based fiber collected by wet spinning of the cellulose-based aqueous colloid, which illustrates the product properties of this colloid spinning; b is the stress-strain parameters of the fiber single filament, i.e., breaking strength and elongation, and the strength of 2.83 cN / dtex is close to the strength of lyocell cellulose fibers prepared based on the laboratory NMMO dissolution process; the fiber morphologies of c and d indicate that the spun fibers have good orientation and integrity.

[0023] Figure 3 This is a comparison chart of the mechanical properties of single cellulose-based fibers prepared by wet spinning of semi-interpenetrating network cellulose-based aqueous colloids in Examples 1-5 and wet spinning of lyocell process (cellulose dissolved in NNMO aqueous solution) in Comparative Example 1, wherein a and b are breaking strength and breaking elongation, respectively, wherein samples 1-5 are fiber strength parameters obtained in Examples 1-5, and sample 6 is the corresponding parameter obtained in Comparative Example 1.

[0024] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION

[0025] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0026] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0027] Embodiment 1:

[0028] A method for preparing a semi-interpenetrating network cellulose-based aqueous colloid is as follows:

[0029] Using dry cotton pulp as raw material, micro / nano fibrillated cellulose was obtained by mechanical crushing and drying, and then a certain amount of fibrillated cellulose was added to a beaker of pure water and stirred continuously to obtain an aqueous suspension of fibrillated cellulose (FC) with good fluidity. Then, a high-pressure homogenizer was used for shear crushing and homogenization (100 MPa) for 30 cycles to obtain a fibrillated cellulose dispersion with a mass fraction of 6 wt%. The fibrillated cellulose dispersion was then heated to 60 o C, and add citric acid in a mass ratio of 0.08 to cellulose, and stir to react to obtain a 6 wt% cellulose aqueous colloidal solution.

[0030] A certain amount of aqueous polymer monomer-acrylamide is dissolved in cellulose aqueous colloid solution, 50 o C and mechanically stirred, and then an initiator potassium persulfate (with acrylamide in a mass ratio of 0.01:1) and a cross-linking agent N,N'-methylenebisacrylamide (with polyacrylamide in a mass ratio of 0.05:1) were added respectively. Under stirring, acrylamide underwent in situ polymerization in the cellulose aqueous colloidal solution to form a polymer network structure. After 6 h of reaction, a cellulose-polyacrylamide semi-interpenetrating network aqueous colloidal solution with a solid content of 10 wt% was obtained, in which the mass ratio of cellulose to polyacrylamide was 3:2.

[0031] The rheological properties of the semi-interpenetrating network cellulose-based aqueous colloid synthesized in Example 1 were tested, and the apparent viscosity of the spinning solution was 18317 mPa·s. The cellulose colloid solution was spun by wet spinning, and the spinning solution was extruded by a syringe pump (3.0 m / min) and then entered into a multi-coagulation bath for washing. After exiting the coagulation bath by a guide roller, it was heat-dried and finally collected by a winding roller (0.5 m / min). There were three groups of multi-coagulation baths, which were 1 wt%, 5 wt% calcium chloride solution and pure water, respectively.

[0032] Embodiment 2:

[0033] A method for preparing a semi-interpenetrating network cellulose-based aqueous colloid is as follows:

[0034] Using dry cotton pulp as raw material, micro / nano fibrillated cellulose was obtained by mechanical crushing and drying, and then a certain amount of fibrillated cellulose was added to a beaker of pure water and stirred continuously to obtain an aqueous suspension of fibrillated cellulose with good fluidity. Then, a high-pressure homogenizer was used for shear crushing and homogenization (100 MPa) for 30 cycles to obtain a fibrillated cellulose dispersion with a mass fraction of 10 wt%. The fibrillated cellulose dispersion was then heated to 60 o C, add citric acid in a mass ratio of 0.08 to cellulose and stir to react to obtain a 10 wt% cellulose aqueous colloidal solution.

[0035] A certain amount of aqueous polymer monomer-acrylamide is dissolved in cellulose aqueous colloid solution, 60 o C and mechanically stirred, and then an initiator potassium persulfate (with acrylamide in a mass ratio of 0.01:1) and a cross-linking agent N,N'-methylenebisacrylamide (with polyacrylamide in a mass ratio of 0.05:1) were added respectively. Under stirring, acrylate was in situ polymerized in the cellulose aqueous colloid network. After 6 h of reaction, a cellulose-polyacrylate semi-interpenetrating network aqueous colloid solution with a solid content of 16.6 wt% was obtained, in which the mass ratio of cellulose to polyacrylate was 3:2.

[0036] The rheological properties of the semi-interpenetrating network cellulose-based aqueous colloid synthesized in Example 2 were tested, and the apparent viscosity of the spinning solution was 80410 mPa·s. The cellulose colloid solution was spun by a dry-wet process. The spinning solution was extruded by an injection pump (3.0 m / min) and then entered into multiple coagulation baths for washing. After exiting the coagulation bath from the guide roller, it was heat dried and finally collected by the winding roller (0.5 m / min). The multiple coagulation baths were divided into three groups, which were calcium chloride solution with a mass fraction of 1 wt%, 5 wt% and pure water, respectively.

[0037] Embodiment 3:

[0038] A method for preparing a semi-interpenetrating network cellulose-based aqueous colloid is as follows:

[0039] Using dry cotton pulp as raw material, micro / nano fibrillated cellulose was obtained by mechanical crushing and drying, and then a certain amount of fibrillated cellulose was added to a beaker of pure water and stirred continuously to obtain an aqueous suspension of fibrillated cellulose with good fluidity. Then, a high-pressure homogenizer was used for high-pressure shear crushing and homogenization (100 MPa) for 25 cycles to obtain a cellulose dispersion with a mass fraction of 14 wt%. The cellulose dispersion was then heated to 60 o C, add citric acid in a mass ratio of 0.08 to cellulose and stir to react to obtain a 14 wt% cellulose aqueous colloidal solution.

[0040] A certain amount of aqueous polymer monomer-acrylamide is dissolved in cellulose aqueous colloid solution, 60 o C and mechanically stirred, and then an initiator potassium persulfate (with acrylamide in a mass ratio of 0.01:1) and a cross-linking agent N,N'-methylenebisacrylamide (with polyacrylamide in a mass ratio of 0.05:1) were added respectively. Under stirring, acrylate was in situ polymerized in the cellulose aqueous colloidal network. After 6 h of reaction, a cellulose-polyacrylate semi-interpenetrating network aqueous colloidal solution with a solid content of 22.3 wt% was obtained, and the mass ratio of cellulose to polyacrylate was 3:2.

[0041] The rheological properties of the semi-interpenetrating network cellulose-based aqueous colloid synthesized above were tested, and the apparent viscosity of the spinning solution was 251237 mPa·s. The cellulose colloid solution was spun by a dry-wet process. The spinning solution was extruded by an injection pump (3.0 m / min) and then entered multiple coagulation baths for washing. After exiting the coagulation bath by a guide roller, it was hot-dried and finally collected by a winding roller (0.5 m / min). The multiple coagulation baths were divided into three groups, which were calcium chloride solution with a mass fraction of 1 wt%, 5 wt% and pure water, respectively.

[0042] Embodiment 4:

[0043] A method for preparing a semi-interpenetrating network cellulose-based aqueous colloid is as follows:

[0044] Using dry bleached hardwood pulp as raw material, micro / nano-fibrillated cellulose was obtained by mechanical crushing. Then a certain amount of fibrillated cellulose was added to a beaker of pure water and stirred continuously to obtain an aqueous suspension of fibrillated cellulose with good fluidity. Then, a high-speed ball mill (zirconia ball diameter 6 mm, speed 120 rpm) was used for 20 cycles of ball milling to obtain a cellulose dispersion with a mass fraction of 6 wt%. The cellulose dispersion was then heated to 60 oC, add glutaraldehyde in a mass ratio of 0.05 to cellulose and stir to react to obtain a 6 wt% cellulose aqueous colloidal solution.

[0045] A certain amount of aqueous polymer monomer-vinyl pyrrolidone is dissolved in a cellulose aqueous colloidal solution, 50 o C and mechanically stirred, and then an initiator azobisisobutyronitrile (with a mass ratio of 0.02:1 to vinyl pyrrolidone) and a cross-linking agent N,N'-methylenebisacrylamide (with a mass ratio of 0.02:1 to polyvinyl pyrrolidone) were added respectively. Under stirring, vinyl pyrrolidone was in situ polymerized in the cellulose aqueous colloidal solution to form a polymer network structure. After 8 h of reaction, a cellulose-polyvinyl pyrrolidone semi-interpenetrating network aqueous colloidal solution with a solid content of 10 wt% was obtained, and the mass ratio of cellulose to polyvinyl pyrrolidone was 3:2.

[0046] The rheological properties of the semi-interpenetrating network cellulose-based aqueous colloid synthesized above were tested, and the apparent viscosity of the spinning solution was 19583 mPa·s. The cellulose colloid solution was spun by wet spinning. The spinning solution was extruded by an injection pump (3.5 m / min) and then entered into a multi-coagulation bath for washing. After exiting the coagulation bath by a guide roller, it was hot-dried and finally collected by a winding roller (0.6 m / min). The multiple coagulation baths were divided into three groups, which were 1 wt%, 5% wt calcium chloride solution and pure water, respectively.

[0047] Embodiment 5:

[0048] A method for preparing a semi-interpenetrating network cellulose-based aqueous colloid is as follows:

[0049] Using dried bamboo pulp as raw material, micro / nano-fibrillated cellulose was obtained by mechanical crushing and drying, and then a certain amount of fibrillated cellulose was added to a beaker of pure water and stirred continuously to obtain an aqueous suspension of fibrillated cellulose with good fluidity. Then, a high-pressure homogenizer was used for high-pressure shear crushing and homogenization (100 MPa) for 40 cycles to obtain a cellulose dispersion with a mass fraction of 6 wt%. The cellulose dispersion was then heated to 60 o C, add sodium alginate with a molar ratio of 0.1 to cellulose and stir to react to obtain a 6 wt% cellulose aqueous colloidal solution.

[0050] A certain amount of aqueous polymer monomer-ethylene oxide is dissolved in a cellulose aqueous colloidal solution, 80 oC and mechanically stirred, and then methyl magnesium bromide (with a mass ratio of 0.06:1 to ethylene oxide) and glutaraldehyde (with a mass ratio of 0.02:1 to polyethylene oxide) as an initiator were added respectively. Under stirring, ethylene oxide occurred in situ polymerization in the cellulose aqueous colloidal network. After 10 h of reaction, a cellulose-polyethylene oxide semi-interpenetrating network aqueous colloidal solution with a solid content of 10 wt% was obtained, and the mass ratio of cellulose to polyethylene oxide was 3:2.

[0051] The rheological properties of the semi-interpenetrating network cellulose-based aqueous colloid synthesized above were tested, and the apparent viscosity of the spinning solution was 18795 mPa·s. The cellulose colloid solution was spun by a dry-wet process. The spinning solution was extruded by an injection pump (5.5 m / min) and then entered multiple coagulation baths for washing. After exiting the coagulation bath by a guide roller, it was hot-dried and finally collected by a winding roller (0.8 m / min). The multiple coagulation baths were divided into three groups, which were calcium chloride solution with a mass fraction of 1 wt%, 5 wt% and pure water, respectively.

[0052] Comparative Example 1:

[0053] In order to compare the mechanical properties of cellulose-based aqueous colloids based on water systems and cellulose-dissolving systems, and further illustrate that cellulose-based fibers developed using green and environmentally friendly water systems meet industry indicators. The comparative spinning solution uses the current industrialized Lyocell process and is compared with the semi-interpenetrating network cellulose-based aqueous colloid spinning solution of Example 1 with a solid content of 10%. The method for preparing the spinning solution and spinning using the traditional Lyocell process in Comparative Example 1 is as follows:

[0054] Dry cotton fiber (cotton pulp) was used as raw material to dissolve in an 86 wt% N-methylmorpholine-N-oxide (NMMO) aqueous solution to prepare a 10 wt% cellulose spinning solution; the dissolved cellulose spinning solution was then extruded through a spinneret (3.5 m / min) into a coagulation bath, where coagulation baths 1 and 2 were 30 wt% and 10 wt% NMMO aqueous solutions, respectively. Finally, the fiber prepared by wet spinning was placed in a water bath for washing to remove residual solvents. After washing, the fiber was further stretched and dried by heat drying to obtain a typical lyocell fiber.

[0055] It should be noted that the spinning processes carried out in the above Examples 1-5 and Comparative Example 1, the obtained fibers have the same thickness and size. The semi-interpenetrating network cellulose-based aqueous colloid material samples and spun fiber samples obtained in the above Examples and Comparative Examples were tested:

[0056] (1) Characterization of colloid rheology: A digital viscometer (SNB-2, China) was used to test the cellulose-based composite aqueous polymer colloid. 50 mL of aqueous colloid was placed in a beaker and allowed to stand for 24 h at room temperature.o The measurement was performed using an L4 rotor at 370 °C and the unit of measurement was mPa·s.

[0057] (2) Characterization of single fiber mechanical properties: The mechanical properties of fibers prepared by cellulose-based aqueous colloid wet spinning were tested using an electronic single yarn strength tester (YM061, China). The clamp distance was set to 30 mm, the tensile speed was fixed at 10 mm / min, and each sample was measured 5 times to take the average value. The dry strength (cN / dtex) and elongation at break (%) were calculated and recorded.

[0058] (3) Characterization of fiber morphology: Scanning electron microscopy (FEI Quanta 200, USA) was used to test the surface and cross-sectional micromorphology of fibers prepared by cellulose-based aqueous colloid wet spinning. Liquid nitrogen brittle fracture treatment was used for complete sample preparation of fiber cross-section.

[0059] The test data of Examples 1-3 are shown in Table 1.

[0060] Table 1

[0061] Result analysis:

[0062] The semi-interpenetrating network cellulose-based aqueous colloids prepared in Examples 1-3 based on the water system and the cellulose-based aqueous colloids with different solid contents prepared using the same cellulose and aqueous polymer all have good spinnability. Figure 1 It can be seen that the aqueous colloids prepared with different cellulose contents (solid contents) have good uniformity and processability. A large number of spinning experiments were further carried out using cellulose-based aqueous colloids with different solid contents as spinning solutions. Through comparison, it was found that the solid content and apparent viscosity of the spinning solution are important indicators that determine whether the aqueous colloid has good spinnability. According to the experimental results, when the solid content of the cellulose-based aqueous colloid is not less than 2 wt% and the viscosity is greater than 12000 mPa·s, the colloid has good spinnability, but when the solid content of the cellulose-based aqueous colloid exceeds 50 wt%, it will be too high to cause continuous spinning. Therefore, the present application prefers that the solid content of the cellulose-based aqueous colloid is 2.3-46 wt%. In addition, the apparent morphology of the cellulose-based fiber prepared by wet spinning in Example 2 was observed by scanning electron microscopy ( Figure 2 (cd) It can be clearly seen that the cellulose-based fibers obtained through multiple stretching treatments such as spinning and drying and stretching have good orientation, which is beneficial to the improvement of the mechanical properties of the fibers.

[0063] The cellulose-based fibers prepared by the cellulose-based aqueous colloid based on the water system of the present invention are compared with the cellulose fibers produced by the current industrialized lyocell process. Figure 3The tensile breaking strength of the cellulose-based fibers prepared in Examples 1-5 of the present invention is 2.98-3.74 cN / dtex, and the breaking strength of the cellulose fibers prepared by the laboratory lyocell process is 2.83 cN / dtex; the corresponding elongation at break is 6.14%-9.16%, respectively, and the latter is 7.3%. Figure 3 It can be seen that the average strength and elongation at break of the fibers obtained by cellulose-based aqueous colloid wet spinning are higher than those of cellulose fibers prepared by the laboratory NMMO process, which further illustrates the feasibility and practicality of the green process of preparing cellulose-based fibers by cellulose-based aqueous colloid spinning based on a water system.

[0064] In summary, the cellulose-based fibers prepared using cellulose-based aqueous colloids have good fiber-forming properties, and the fiber mechanical properties meet current industry indicators.

[0065] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.

Claims

1. A method for preparing a semi-interpenetrating network cellulose-based aqueous colloid material for spinning, characterized in that: The following steps are involved: S1. Using cellulose pulp as raw material, obtaining micro / nano-fibrillated cellulose of uniform fineness by mechanical shearing, then preparing an aqueous suspension of fibrillated cellulose with water as solvent, and then obtaining a non-derivatized fibrillated cellulose dispersion with a solid content of 2-20 wt% by homogenization; S2, adding a crosslinking agent to the fibrillated cellulose dispersion obtained in step S1, and stirring the mixture at a constant temperature to obtain a uniform cellulose aqueous colloidal solution having a solid content of 2.1-24 wt%, wherein the cellulose aqueous colloidal solution is a network crosslinked solution based on covalent bonds or hydrogen bonds between cellulose and the crosslinking agent, wherein the mass ratio of cellulose to the crosslinking agent is 1:0.05-1:0.2, and the crosslinking agent is at least one of epichlorohydrin, glutaraldehyde, tannic acid, citric acid, sodium alginate, calcium chloride, and ferrous chloride; S3, using the cellulose aqueous colloid solution obtained in step S2 as the first component - cellulose aqueous solution, adding monomers or prepolymers of aqueous polymers into the first component - cellulose aqueous solution, stirring and dissolving, and adding initiators and cross-linking agents, so that the monomers or prepolymers of aqueous polymers are in situ polymerized and cross-linked in the first component - cellulose aqueous solution under the action of the initiators and cross-linking agents to form a second component - polymer network, and finally obtaining a semi-interpenetrating network cellulose-based aqueous colloid with certain spinnability, wherein the mass ratio of cellulose to aqueous polymer is 1:0.1-1:1, and the solid content of the obtained semi-interpenetrating network cellulose-based aqueous colloid is 2.3-46 wt%.

2. The method for preparing a semi-interpenetrating network cellulose-based aqueous colloid material for spinning according to claim 1, characterized in that: The cellulose pulp in step S1 is any one of wood pulp, cotton pulp, bamboo pulp, hemp pulp and straw pulp, or is bacterial cellulose.

3. The method for preparing a semi-interpenetrating network cellulose-based aqueous colloid material for spinning according to claim 1, characterized in that: The mechanical shearing treatment in step S1 is one or more of high pressure homogenization, disc milling, ball milling, pulverizer crushing, steam explosion, twin screw kneading, and mechanical stirring crushing.

4. The method for preparing a semi-interpenetrating network cellulose-based aqueous colloid material for spinning according to claim 1, characterized in that: In step S2, the temperature of the constant temperature stirring is 20-90 o C, time is 4-24 h.

5. The method for preparing a semi-interpenetrating network cellulose-based aqueous colloid material for spinning according to claim 1, characterized in that: In step S3, the aqueous polymer is any one of polyacrylamide, polyvinyl pyrrolidone, polyethylene oxide, polyethylene glycol, sodium polyacrylate, and polyvinyl alcohol.

6. The method for preparing a semi-interpenetrating network cellulose-based aqueous colloid material for spinning according to claim 1, characterized in that: In step S3, the mass ratio of the aqueous polymer monomer to the initiator is 1:0.005-1: 0.015, the mass ratio of water-based polymer to cross-linking agent is 1:0.01-1:0.

2.

7. The method for preparing a semi-interpenetrating network cellulose-based aqueous colloid material for spinning according to claim 1, characterized in that: In step S3, the initiator is at least one of potassium persulfate, sodium persulfate, azobisisobutyronitrile, and methylmagnesium bromide, and the cross-linking agent is at least one of N,N'-methylenebisacrylamide and glutaraldehyde.

8. A semi-interpenetrating network cellulose-based aqueous colloid material, characterized in that: The method is prepared by any one of claims 1 to 7.

9. Use of the semi-interpenetrating network cellulose-based aqueous colloid material according to claim 8 in spinning.

Citation Information

Patent Citations

  • Method for preparing cellulose / butyl methacrylate (BMA) graft copolymer oil absorbent fibers

    CN102766917A

  • Encapsulated and networked regenerated cellulose phase-change fiber and preparation method thereof

    CN106048761A

  • Preparation method of composite fiber of cellulose nanometer fibrils / alginate

    CN106521706A

  • High-flux forward-osmosis hollow fiber membrane and preparation method thereof

    CN109304107A

  • Preparation method and application of nanocellulose polymer optical composite hydrogel

    CN112851972A

Cited By

  • Nanocellulose-based fiber as well as preparation method and application thereof

    CN119859864A

  • Nanocellulose-based fibers, methods for their production and use

    CN119859864B

  • Preparation method of anticoagulant super absorbent resin

    CN120059089A